Information support for business activities on the basis of a systematic approach - Irina Eremina (Sustainable Development and Engineering Economics, 2022)
The study presents a solution to the urgent research problem related to improving information support for the regulation of business activities. Theoretical aspects of its development were studied, and it was found that modern information technologies are the source and cause of the necessary transformations, both in society and in business. Scientists have argued that the process of organising information support includes a continuous analysis of basic information for business activities from both internal and external sources in the market environment. The structure and content of the systematic approach were adapted to organise the information support for the regulation of business activities. Using this approach, the information support system is captured as part of a single management system capable of ensuring the interaction of the managerial link of the business entity with external sources of information support. Further, a systematic approach is applied in conducting the functions of the regulatory process, that is, planning, organising, accounting, analysing, controlling, as well as implementing the interaction of structural elements. We conducted quality diagnostics of the parameters of information support for business entities. Based on the results of the survey, the necessary parameters were selected, and the coefficient of the quality of the information support for the regulation of business activities was determined. We offer recommendation based on the quality coefficients of information support for these business entities.